2017
DOI: 10.1016/j.ecolecon.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Tenure Security, Human Capital and Soil Conservation in an Overlapping Generation Rural Economy

Abstract: We develop an overlapping generation model of rural agricultural households to examine whether tenure security and subsistence needs influence the choice between unexploited topsoil and investment in children's human capital as the mode of transfer of wealth. A unique dataset from Bangladesh finds that tenure security is associated with greater topsoil conservation and lower human capital investment. Therefore, there exists a tradeoff between these two modes of transfer. We suggest that increased public expend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The longer the tenure period is, the more stable farmers’ expectation of long-term investments will be and they are more likely to make long-term investments and adopt green agricultural technology [ 43 ]. Long-term and stable land tenure can improve farmers’ behavior expectations and help them to recover investment costs and obtain benefits from long-term agricultural investment, which has an incentive effect on farmers’ long-term investment [ 44 , 45 ]. Studies have shown that short-term contracts will induce farmers to engage more in short-term production behavior, which is not conducive to farmers’ long-term land investment [ 46 ].…”
Section: Theoretical Analysis and Hypotheses Developmentmentioning
confidence: 99%
“…The longer the tenure period is, the more stable farmers’ expectation of long-term investments will be and they are more likely to make long-term investments and adopt green agricultural technology [ 43 ]. Long-term and stable land tenure can improve farmers’ behavior expectations and help them to recover investment costs and obtain benefits from long-term agricultural investment, which has an incentive effect on farmers’ long-term investment [ 44 , 45 ]. Studies have shown that short-term contracts will induce farmers to engage more in short-term production behavior, which is not conducive to farmers’ long-term land investment [ 46 ].…”
Section: Theoretical Analysis and Hypotheses Developmentmentioning
confidence: 99%
“…Examinations of livelihood strategies [for e.g. 90,98, 127,128] have revealed that although the rural poor may have limited resources, they still have considerable capacity to adapt to environmental degradation, either by mitigating its effects on their livelihoods or by rehabilitating degraded resources [117]. A wide variety of coping mechanisms may be used to deal with environmental stress [117].…”
Section: Poverty and Environmental Stewardshipmentioning
confidence: 99%
“…Achieve universal primary education 3. Promote gender equality and empower women  Environmental degradation contributes to an increased burden on women and children (especially girls) in terms of the time required to collect water and fuelwood, thus reducing the time they have available for education or income-generating activities  Including the environment within the primary school curriculum can influence the behaviour of young people and their parents, thereby supporting sustainable livelihoods  Women often have limited roles in decision-making, from the community level to national policymaking, which prevents their voices from being effectively heard, particularly with respect to their environmental concerns  Women often have unequal rights and insecure access to land and natural resources, limiting their opportunities and ability to access productive assets Many studies and institutions that follow the idea of Brundtland Commission, that poverty alleviation issue has to tackle before environmental degradation [25,95,96,100,127,130,131,132], may promote the idea of following and adopting the policies that do not acknowledge the different meanings of environment to marginalized sections, and macroeconomic responses that may increase both environmental degradation and poverty in rural and urban settings [97]. Contrary to this, our experience suggests that acknowledging the local rather than universal experience of povertyenvironment nexus will be important and to provide favourable conditions for marginalised section to create their own institutional response to environmental changes , which currently operates in eleven countries in Africa, Asia and Central America [11,12].…”
Section: Relationships Between Urban Poverty and Environmental Degradmentioning
confidence: 99%